Pregnancy rate and associated factors in dairy cows of Bangladesh (Bangladesh Veterinarian, 2019)
The study was undertaken to identity the factors affecting the pregnancy rate in cows of commercial dairy farms in Bangladesh. Pre-tested questionnaires were used for collecting data from 662 mixed breed cows of 22 commercial dairy farms. The overall pregnancy rate was 53.6%. Pregnancy rate was the highest (62.5%) in local breed (P